CSR Reports, CSR Disclosure Quality, and Corporate Reputations: A Systematic Literature Review - Berto Usman (Universitas Pasundan, 2020)
This paper provides a critical review of the literature addressing the relationships between corporate social responsibility (CSR) reports, their disclosure quality, and their effects on corporate reputation. CSR reports are deemed important to legitimate a company's existence with its stakeholders. However, there is a debate around the use of this form of voluntary disclosure as the sole means of managing corporate reputation. To prepare for the emerging discourses, this study draws upon 90 papers published in leading academic journals, discussing related topics from the early 1990s to 2018. Hence, this paper proposes for discussion of two major research questions: (1) whether CSR reports are associated with corporate reputations and (2) whether the quality of CSR disclosures is associated with corporate reputations. Along with the two proposed questions, the potential premise for a future empirical test is presented in a systematic exhibition.